1985
DOI: 10.1139/x85-152
|View full text |Cite
|
Sign up to set email alerts
|

A multifactor ecological classification of the northern hardwood and conifer ecosystems of Sylvania Recreation Area, Upper Peninsula, Michigan

Abstract: An ecological method of multifactor ecosystem classification was applied in the Sylvania Recreation Area, an 8500-ha tract of old-growth northern hardwood – conifer forests in upper Michigan. The uplands and wetlands were subjectively classified into 25 ecosystems by a method combining reconnaissance, plot sampling, data analysis, and ecosystem mapping. Each ecosystem was a characteristic combination of physiography, ecological species groups (ground vegetation), and soil. Discriminant analysis was used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 0 publications
2
42
0
1
Order By: Relevance
“…However, mF was a poorer predictor of site index compared to SWC. This is consistent with the hypothesis that soil water capacity is better assessed by soil parameters than floristic indices, especially because tree productivity can be affected by deeper soil horizons whereas the shallow-rooted herb-layer vegetation is not [37,50].…”
Section: Are Abiotic and Floristic Indices Complementarysupporting
confidence: 89%
See 3 more Smart Citations
“…However, mF was a poorer predictor of site index compared to SWC. This is consistent with the hypothesis that soil water capacity is better assessed by soil parameters than floristic indices, especially because tree productivity can be affected by deeper soil horizons whereas the shallow-rooted herb-layer vegetation is not [37,50].…”
Section: Are Abiotic and Floristic Indices Complementarysupporting
confidence: 89%
“…This is consistent with the hypothesis that neither vegetation nor physiography alone are sufficient to classify ecosystems or to reliably predict site index [17,27,50,58]. Nieppola [43] showed that the inclusion of soil type in the prediction model increases the accuracy of site index estimation by about 15%.…”
Section: Are Abiotic and Floristic Indices Complementarysupporting
confidence: 77%
See 2 more Smart Citations
“…Quantitative analysis of patterns of soil-site factors in relationship to plant communities has proven valuable in the development of ecological classifications in similar ecological regions in the province of New Brunswick, Canada (Zelazny et al 1989) and in the Lake States (Pregitzer and Barnes 1984;Spies and Barnes 1985;Host et al 1988). This methodology is being used to help delineate units of land with a unique combination of potential natural community, soil, landscape features, and climate, and which differ from other units in their ability to produce vegetation and respond to management.…”
Section: Introductionmentioning
confidence: 99%